Do Teacher-Coaches Make the Cut? The Effectiveness of Athletic Coaches as Math and Reading Teachers - Anna Jacob Egalite; Daniel H. Bowen; Julie R. Trivitt (Arizona State University, 2015)
Math and reading teachers who also coach athletics in the public school system are challenged to balance the responsibilities that come with fulfilling dual occupational roles. While many studies have examined teacher-coaches' stress levels and job perception in the context of role strain, there is no evidence of how student achievement in tested subjects is affected by assignment to these teacher-coaches. A large administrative panel data set provided by the Florida Department of Education allows us to match students to teachers and use a student fixed effects approach to track changes in math and reading test scores over a seven-year time period, from 2002 through 2009. Despite the challenges associated with holding dual occupational roles, we find that students assigned to teacher-coaches perform at the same level in reading and math as when they are assigned to non-coaching teachers.